Public Employment Policy Professionals in Industrialized Countries: Different Contexts and Similar Practices - Provencher, Ysabel; Richard, Marie-Claude (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2010)
Based on a review of predominantly French, Canadian and American literature thisarticle deals with employment coaching of populations excluded from the labourmarket. This is a new function that emerged from the activation of public employmentpolicies over the past few years, and has become now the principal mode ofcommitment of the state towards populations excluded from the labour market.Focusing on the discourse and practices of counselling professionals, concerningthe development of this function, the article highlights the impact of transactionsbetween agents of public policy and their clients on the effects of reforms to socialassistance programs. While day to day practices vary among coaching providersaccording to their specific environments, the literature review shows a convergenceof practices among agents of public, private or community employment policies inthe use of their own social networks, the constraints they encounter and the strongrelational aspects they associate with their counselling function. In concluding, thearticle notes a lack of awareness of their roles as intermediaries in the labourmarket, in and in particular about their use of organisational procedures, strategies,and rationale for their actions.S'appuyant sur une recension d'kcrits principalement fran~aisc, anadiens et amCricains,cet article traite de l'accompagnement en emploi des populations excluesdu march6 du travail, une fonction ayant emerge de l'activation des politiques.Public Employlnent Policy Professionals in Industrialized Countriespubliques de l'emploi des dernikres annkes et qui devient le principal moded'engagement de l ' ~ t a t envers les populations exclues du march6 du travail. Ens'attardant particulikrement aux discours des professionnels de l'accompagnementsur la mise en oeuvre de cette fonction, I'article souligne le rBle des transactionsentre les agents des politiques publiques et leurs clients sur les effets des reformesdes regimes d'aide sociale. Bien que les pratiques quotidiennes des charges d'accompagnementdiffkrent selon les contextes specifiques dans lesquels elles s'inscrivent,des etudes recensges indiquent une convergence des discours des agents des servicespublics, prives ou associatifs des politiques de l'emploi en ce qui a trait 5 l'utilisationde leur rCseau social, aux contrainces qu'ils rencontrent ainsi qu'5 la fortedimension relationnelle qu'ils associent 2 la fonction d'accomnpagnement. Particlese conclut en constatant le manque d'information lie ii ces acteurs interlnkdiairesdu march6 du travail, notamment sur leurs modes d'organisation, leurs strategies etles justifications de leurs actions.